Subharmonics of a Nonconvex Noncoercive Hamiltonian System - Kallel, N.; Timoumi, М. (Український математичний журнал, 2003)
We study the problem of the existence of multiple periodic solutions of the Hamiltonian system Jx˙+u∇G(t,u(x))=e(t), where u is a linear mapping, G is a C¹-function, and e is a continuous function.